2003
DOI: 10.1021/jf0304021
|View full text |Cite
|
Sign up to set email alerts
|

Anthocyanin Profile of Korean Cultivated Kidney Bean (Phaseolus vulgaris L.)

Abstract: This investigation was conducted to determine the structures and amounts of anthocyanins obtained from seed coats of kidney bean (Phaseolus vulgaris L.) cultivated in Korea. Anthocyanins in the seed coat of kidney bean were extracted with 1% HCl/20% CH(3)OH, and the crude anthocyanin extracts were purified by semipreparative HPLC. Five major anthocyanins were isolated, and their chemical structures were identified by spectroscopic methods (UV-vis, LC/ES-MS, and 1H and 13C NMR). The structures of these five ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
62
1
6

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(79 citation statements)
references
References 16 publications
10
62
1
6
Order By: Relevance
“…The amount of anthocyanin in the black soybean variety of G2 in the present study is higher than those in nine other black soybean varieties cultivated in Korea, but lower than one variety of YJ 100-1 (Choung et al 2001). Black soybeans analyzed in the present study contain more diverse kinds of anthocyanins than rice varieties (AbdelAal et al 2006;Kim et al 2008), corn, wheat or barley varieties (Abdel-Aal et al 2006), kidney bean varieties (Choung et al 2003) and other Korean black soybean varieties (Choung et al 2001). In addition, slightly different chromatograms of 9 anthocyanins were reported recently in Cheongja 3 variety of black soybean (Lee et al 2009) grown in Korea.…”
Section: Resultsmentioning
confidence: 42%
“…The amount of anthocyanin in the black soybean variety of G2 in the present study is higher than those in nine other black soybean varieties cultivated in Korea, but lower than one variety of YJ 100-1 (Choung et al 2001). Black soybeans analyzed in the present study contain more diverse kinds of anthocyanins than rice varieties (AbdelAal et al 2006;Kim et al 2008), corn, wheat or barley varieties (Abdel-Aal et al 2006), kidney bean varieties (Choung et al 2003) and other Korean black soybean varieties (Choung et al 2001). In addition, slightly different chromatograms of 9 anthocyanins were reported recently in Cheongja 3 variety of black soybean (Lee et al 2009) grown in Korea.…”
Section: Resultsmentioning
confidence: 42%
“…It was reported that kaempferol glycosides are hepatoprotectant and inhibit α-glucosidase [24,25]. Anthocyanins and proanthocyanidins from adzuki bean were found to have strong antioxidant activity [26,27]. Common beans with high antioxidant activity may contain large amounts of kaempferol-3-O-glucoside, which is synthesized by key enzymes flavonol synthase and glycosyltransferase or substantial quantities of cyanidin glycosides synthesized by dihydroflavonol 4-reductase, anthocyanidin synthase, and glycosyltransferase.…”
Section: Polyphenol Compounds In Common Beansmentioning
confidence: 99%
“…Of these, 3-O-glucosides of delphinidin, petunidin and malvidin had been previously isolated from black beans (Aparicio-Fernades & Garica-Gasca et al, 2006;Aparicio-Fernades & Yousef et al, 2005;Romani et al, 2004;Takeoka et al, 1997). Pelargonidin 3-O-glucoside and cyanidin 3-O-glucoside had been previously reported to exist in red kidney beans (Choung et al, 2003). Based on the data presented in Table 2, the trace peaks A-4, A-8 and A-7 of small red beans were tentatively identified as pelargonodin 3,5-O,O-diglucoside, pelargonidin 3-O-(6″-malonyl)glucoside and cyandin 3-O-(6″ -malonyl) glucoside, respectively.…”
Section: Identification Of Bean Flavonoidsmentioning
confidence: 99%
“…There are 10 major US commercial market classes of dry beans: black beans (Aparicio-Fernades et al, 2006;Aparicio-Fernandez, Yousef, Loarca-Pina, Gonzales de Mejia, & Lila, 2005;Takeoka et al, 1997), pinto beans (Beninger et al, 2005;Beninger & Hosfield, 2003), light and dark red kidney beans (Beninger & Hosfield, 1999;Choung, Choi, An, Chu, & Cho, 2003), pink beans, navy beans, great northern beans (Kelly et al, 2003;Luthria & Pastor-Corrales, 2006), alubia beans (Kelly & Copeland, 1998;Kelly, Hosfield, Varner, Uebersax, & Taylor, 1999) cranberry beans (Beaver, 1999), and small red beans, also known as redMexican beans (Hosfield, Varner, Uebersax,& Kelly, 2004). Common dry beans contain a wide range of flavonoids, including flavonols, their glycosides, anthocyanins, proanthocyanidins, and isoflavones, as well as some phenolic acids (Aparicio-Fernades & Garica-Gasca et al, 2006;Aparicio-Fernades & Yousef et al, 2005;Beninger & Hosfield, 1999;Beninger & Hosfield, 2003;Choung et al, 2003;Diaz-Batalla, Widholm, Fahey, Casano-Tostado, & Paredes-López, 2006;Macz-Pop, González-Parama´s, Pérez-Alonso, & Rivas-Gonzalo, 2006;Romani et al, 2004;Takeoka et al, 1997) (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%